Age-specific changes in the serum proteome of female anadromous, hilsa Tenualosa ilisha: a comparative analysis across developmental stages - Chakraborty, Hena; Chakraborty, Hirak Jyoti; Das, Basanta Kumar; Maity, Joydev (Frontiers in Immunology, 2024)
The investigation of the proteome profile of the female HilsaHilsa (Tenualosa ilisha), a species of great ecological and economic importance, was conducted across a range of age groups in order to comprehend the functional dynamics of serum proteome for the purposes of conservation and aquaculture as well as to sustain the population. Applying advanced LC-MS/MS base proteomics, including bioinformatics analysis of serum proteome levels show different proteins associated with GO terms, and the genes and associated enriched KEGG pathways (e.g., phagosome, mTOR, Apelin signalingbased proteomics data was analysed and submitted the data in proteomeXchange Consortium via PRIDE., including Bbioinformatics analysis of serum proteome also haves been done and it, showed different proteins associated with GO terms, and the genes associated with enriched KEGG pathways (e.g., phagosome, mTOR, Apelin signalling pathways, herpes simplex virus etc.) that are implicated in immune responses. Significant age-dependent differences were found in the expression levels of important immunological proteins, such as those pertaining to cellular defense, inflammatory response. In this study, we annotated 952, 494, 415 and 282 proteins in the year class IV to class I HilsaHilsa and analysed their PPI (protein-protein interaction) networks with respect toconcerning their functional characteristics. It was noticed that from class I to class IV, new proteins were appearing and it wasappeared and were more than three foldthree-fold. Notably, Formatted: Not Superscript/ Subscript year class-I, displayed a lower abundance of proteins compared to year class-IVclass I displayed a lower abundance of proteins compared to year class IV HilsaHilsa, which displayed higher quantities of proteins. This is the first study to report on the analysis of the serum proteome of HilsaHilsa at different developmental stages, and the results can help to improve the comprehension of the mechanisms underlying the different changes in protein enrichment that occur during migration in HilsaHilsa. This analysis also offers important insights into immune systemsthe immune system for the conservation and management of HilsaHilsa.